Pengembangan Program Ekstrakurikuler Kreatif dan Inovatif untuk Meningkatkan Minat Belajar Siswa SMK: Development of Creative and Innovative Extracurricular Programs to Enhance Vocational High School Students’ Learning Interest - hilmi, wildan (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
This study examines the development of creative and innovative extracurricular programs to enhance students' learning interest at SMK Al-Falah Nagreg Bandung. In the modern era, the decline in learning interest at the vocational high school level is a major concern. The research aims to identify the impact of these extracurricular programs on students' learning interest and formulate recommendations for improving education at SMK Al-Falah Nagreg Bandung. Using a qualitative field approach, data were collected through interviews, observations, and document analysis. The findings show that the creative and innovative extracurricular programs have positively influenced students' learning interest, leading to increased engagement, creativity, social involvement, and academic achievement. Recommendations include further development of the extracurricular programs, instructor training, regular evaluation, parental and community involvement, and sharing research findings with other schools. The study aims to guide SMK Al-Falah Nagreg Bandung in improving education quality and motivating students to actively participate in the learning process. Furthermore, successful implementation of these programs can serve as a model for other vocational high schools facing similar challenges in student engagement. Keywords: Program Development, Extracurricular, Creative, Innovative, Interest in Learning.   Abstrak: Penelitian ini membahas pengembangan program ekstrakurikuler kreatif dan inovatif sebagai upaya untuk meningkatkan minat belajar siswa di SMK Al-Falah Nagreg Bandung. Dalam konteks pendidikan di era modern, penurunan minat belajar di tingkat sekolah menengah kejuruan menjadi perhatian utama. Tujuan penelitian ini adalah untuk mengidentifikasi dampak program ekstrakurikuler tersebut terhadap minat belajar siswa dan merumuskan saran-saran untuk perbaikan pendidikan di SMK Al-Falah Nagreg Bandung. Penelitian ini menggunakan pendekatan kualitatif lapangan dengan mengumpulkan data melalui wawancara, observasi, dan analisis dokumen. Hasil penelitian menunjukkan bahwa program ekstrakurikuler kreatif dan inovatif telah memberikan dampak positif dalam meningkatkan minat belajar siswa. Siswa yang terlibat dalam program tersebut melaporkan peningkatan minat belajar, pengembangan kreativitas, peningkatan keterlibatan sosial, dan pencapaian akademik yang lebih baik. Saran yang diusulkan meliputi pengembangan lebih lanjut program ekstrakurikuler, pelatihan instruktur, evaluasi rutin, partisipasi orang tua dan masyarakat, serta berbagi hasil penelitian dengan sekolah-sekolah lain. Diharapkan hasil penelitian ini dapat memberikan panduan bagi SMK Al-Falah Nagreg Bandung dalam meningkatkan kualitas pendidikan dan memotivasi siswa untuk aktif terlibat dalam proses belajar. Kata Kunci: Pengembangan Program, Ekstrakurikuler, Kreatif, Inovatif, Minat Belajar.